Cataract and its risk factor among adults residing in South Bihar, India - Gupta, Shiwani; Gupta, Animesh; Nehal, M.; Pandey, Kalyani; Kreesna, Ananta; Shakir, Tahreem; Chaudhary, Jagmohan; Puneet, Priyanka; Sangeeta, Kumari (International Journal of Research in Medical Sciences, 2020)
Background: Cataract is considered as one of the most common causes of visual impairment and the leading cause of blindness in the world. Age related cataract occurs in people above 50 years of age and the its pathogenesis is multifactorial. Therefore, the present study was aimed to assess the prevalence and risk factors for cataract. Methods: Community based cross sectional study was conducted among adults residing at urban areas of South Bihar. The data was collected by interview method, using pre-tested semi-structured questionnaire which contains socio-demographic data, dietary habits, history of diabetes or hypertension, family history of cataract and long-term sun exposure. Results: Among 240 participants, 94 (39.2%) were male and 146 (60.8%) were female. Maximum participants were aged more than 70 years. The prevalence of cataract was 52.1%. Conclusions: The prevalence of cataract was quite high and was significantly associated with age, long term sun exposure and family history of cataract.